Cebrennus Simon, 1880 (Araneae: Sparassidae): a revisionary up-date with the description of four new species and an updated identification key for all species - Jäger, Peter (Zootaxa, 2014)
The spider genus Cebrennus Simon, 1880 is revised again after thirteen years. Four new species are described: Cebrennus atlas spec. nov. from Morocco (female), C. flagellatus spec. nov. from Afghanistan (male), C. laurae spec. nov. from Canary Islands (male), and C. rechenbergi spec. nov. from Morocco (male and female). Cebrennus clercki (Audouin, 1826) comb. nov. is transferred from Philodromidae to Sparassidae and considered a nomen dubium. The holotype of C. aethiopicus Simon, 1880 is illustrated for the first time. Cebrennus tunetanus Simon, 1885 is re-described by illustrating its copulatory organs and some somatic characters, the internal duct system is shown for the first time supporting its placement in Cebrennus. An updated identification key for all species is provided. New records of Cebrennus species are listed: C. wagae (Simon, 1874) is recorded from Libya and Malta for the first time, the latter representing the first record for the entire genus from Europe. C. kochi (O. Pickard-Cambridge, 1872) is recorded from Syria, C. aethiopicus from Sudan for the first time. Records from the Canary Islands and from Afghanistan extend the known generic distribution range further to the West and East. Behavioural aspects (burrowing, escaping, mating) of C. rechenbergi and partly of C. villosus (Jézéquel & Junqua, 1966) are described. Photographs of this behaviour as well as of the habitus of several species are provided.